2020
DOI: 10.3389/fonc.2020.01199
|View full text |Cite
|
Sign up to set email alerts
|

A Multiple Primary Malignancy Patient With FANCA Gene Mutation: A Case Report and Literature Review

Abstract: Background: Multiple primary malignancies (MPMs) refer to two or more primary malignant tumors in the same individual, the prevalence of which ranges from 0. 734 to 11.7%. The risk factors for MPMs vary and include both genetic and environmental causes. FANCA gene mutation might be a predisposition to the development of a second primary cancer. Here, we report a case in which a patient with a FANCA mutation developed thyroid papillary carcinoma and gastric adenocarcinoma. Case Presentation: A 48-year-old woman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The authors speculated that because FANCA is involved in mismatch repair, it can increase the mutational rate and lead to the development of multiple tumours. We propose that a similar effect could have caused the metastatic behaviour of ameloblastoma in our study [ 55 ]. To our knowledge, this is a first report of a mutation in this gene in a patient with ameloblastic tumour.…”
Section: Discussionmentioning
confidence: 71%
“…The authors speculated that because FANCA is involved in mismatch repair, it can increase the mutational rate and lead to the development of multiple tumours. We propose that a similar effect could have caused the metastatic behaviour of ameloblastoma in our study [ 55 ]. To our knowledge, this is a first report of a mutation in this gene in a patient with ameloblastic tumour.…”
Section: Discussionmentioning
confidence: 71%
“…Although germline mutations in FANC genes have been reported to increase risk for developing both hematological and solid cancers (32)(33)(34), their roles in tumorigenesis of multiple primary malignancies are largely unknown. A previous case study demonstrated that a germline FANCA mutation (p.Q405*) might be a predisposition to double primary malignancies of thyroid cancer gastric adenocarcinoma (35). These findings suggest that FANCA mutations may be a risk factor for multiple primary malignancies.…”
Section: Casementioning
confidence: 80%
“…Therefore, tislelizumab might be a promising treatment option for mUC patients with PD-L1-negative, MSS and TMB-H. Germline mutation of FANCA was found in our case. Germline FANCA mutation is the most prevalent in patients with Fanconi anemia (FA) but is less reported in patients with solid tumors [9]. Heterozygous FANCA mutation increases the susceptibility to cancers in a sporadic manner in non-FA patients [10].…”
Section: Discussionmentioning
confidence: 99%